2019
DOI: 10.1186/s12944-019-1078-4
|View full text |Cite|
|
Sign up to set email alerts
|

Fat necrosis in the Breast: A systematic review of clinical

Abstract: Breast fat necrosis (FN) originates from aseptic fat saponification, which is a typical lipid cyst or a spiculated lesion called mammographic presentation which mimics malignancy. In order to avoid biopsy, it would be necessary to identify the spectrum of fat necrosis appearances. A systematic research was conducted in October 2018 by using PubMed, MEDLINE, Embase, Google Scholar databases and Google to search for science literature published after 2004. Therefore, the aim of this systematic review, it is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Fat necrosis is a complication causing symptoms in the patient and sometimes requiring biopsy to differentiate it from malignancy. Fat necrosis occurs from 4.6 to 100%, depending on the surgical procedure [16,17]. Our surgical method reported a lower fat necrosis rate (3.4%) than that of traditional BCS because it either did not make or minimized pedicled fat flap.…”
Section: Discussionmentioning
confidence: 81%
“…Fat necrosis is a complication causing symptoms in the patient and sometimes requiring biopsy to differentiate it from malignancy. Fat necrosis occurs from 4.6 to 100%, depending on the surgical procedure [16,17]. Our surgical method reported a lower fat necrosis rate (3.4%) than that of traditional BCS because it either did not make or minimized pedicled fat flap.…”
Section: Discussionmentioning
confidence: 81%
“…Hassan et al [10] studied the specific imaging features of fat necrosis and concluded that the presence of fat signal intensity within the lesion on unenhanced MR images had sensitivity of 98.04%, specificity of 100%, PPV of 100%, and NPP of 96.88%. Vasei et al [3] stated that fat necrosis usually appeared isointense to the fat elsewhere in the breast, it appeared of high SI on T1WI and hypointense on STIR images when compared with the surrounding fat, and this is known as the black hole sign. This is concordant with our results where the presence of fat SI within the lesion had 100% sensitivity, 90.9% specificity, and 96.2% accuracy in differentiating fat necrosis from recurrent breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery and radiation therapy made treated breast prone to several modifications. This can complicate the interpretation of ultrasound and mammographic images, especially when local recurrence is suspected [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the extremely rare causes of fat necrosis is calciphylaxis, which is a calcification of small‐ and medium‐sized arteries leading to the development of intramural thrombus and subsequent ischemia. Calciphylaxis has been reported in the literature to be encountered in different parts of the body like skin, kidneys, muscles, and to a lesser extent in lungs, heart, and alimentary tract 1–4 . It is classified into (A) uremia‐induced and (B) nonuremic‐induced calciphylaxis (obesity, chronic liver disorders, and drugs) 5 .…”
Section: Introductionmentioning
confidence: 99%